"Closing in" the circle with new researchers in astronomy - Gangui, Alejandro (2005)
Having high school students work with professional astronomers in a favorable environment, such as in a research institute or university physics department, may lead to surprising results. This article describes a program in which high school students in Argentina worked with astronomy researchers on a common project and then published their findings.